THE APPLICATION OF PARTICIPATORY PROSPECTIVE ANALYSES TO DEVISE WOMEN EMPOWERMENT PROGRAMS FOR REDUCING POVERTY: CASE STUDY IN SOUTH BENGKULU REGENCY, BENGKULU PROVINCE, INDONESIA - Erni, Agustina; Sitepu, Pribuiarta N.; Gunawan, Indra; Adiprasetyo, Teguh; Mersyah, Rohidin (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2015)
This study is intended to apply participatory prospective analysis to formulate women empowerment programs andÂ activities to reduce poverty. Participatory prospective analysis may facilitate the process of integrating multiplestakeholdersâ preferences in public policy decision since the involvement of stakeholders as part of the povertyÂ alleviation solution; it can be expected to increase the effectiveness of the programs and activities. This study wasconducted in South Bengkulu Regency, Bengkulu Province, Indonesia. Data were collected through focus groupÂ discussion (FGD). A number of 23 participants from various delegates of stakeholders including head or officers ofregency government and its regional working units, non government organizations, community groups and localÂ university were involved in the FGD. Data were analysed using participatory prospective method. The results revealthat there are 15 factors identified shaping the system of women empowerment for poverty reduction. By using a fourquadrantÂ window, those factors are grouping into four categories: input, stakes, unused, and output, as the key of theÂ empowered programs. Input factors are human resource skills, social cultural, formal education attainment andÂ health status. The stakes are access to natural resources, access to capital, local policies and access to decisionmaking process. While the unused factors are past experiences, infrastructure and technology. The outputs areÂ employment, community empowerment, motivation, and job availability. This study shows that the strategy to reducepoverty have to be done via women empowerment programs, which are comprising better off education, skillÂ development, health status and social culture. Access to education, skills and health should be part of the poor asset.Poor women need to equip with assets to reduce their vulnerabilities.